2014
DOI: 10.1097/acm.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Residency Choice and Participation in an Extracurricular Longitudinal Medical School Program to Promote Practice With Medically Underserved Populations

Abstract: Supporting student interest in underserved careers is associated with higher rates of graduates entering primary care residencies, specifically family medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Medical student specialty choice is a dynamic decision influenced by decades of life experiences before medical school and many elements during medical school. 14,18 The results of this study are consistent with previous research indicating that student interest in family medicine upon entry to medical school is strongly predictive of eventual family medicine specialty choice. This study adds to previous literature by quantitatively evaluating the impact of medical student experiences during medical school, particularly family medicinefocused extracurricular activities, which are intended to support and build student interest in family medicine.…”
Section: Discussionsupporting
confidence: 89%
“…Medical student specialty choice is a dynamic decision influenced by decades of life experiences before medical school and many elements during medical school. 14,18 The results of this study are consistent with previous research indicating that student interest in family medicine upon entry to medical school is strongly predictive of eventual family medicine specialty choice. This study adds to previous literature by quantitatively evaluating the impact of medical student experiences during medical school, particularly family medicinefocused extracurricular activities, which are intended to support and build student interest in family medicine.…”
Section: Discussionsupporting
confidence: 89%
“…The importance and value of mentorship is something that is being increasingly appreciated in medicine. [29][30][31] Mentors and primary care faculty in different training sites will have multiple aspects to their jobs, and additional exposure to full-time primary care physicians may help to give residents a more complete understanding of what a fulltime career in primary care might entail for them. Conversely, depending on the goals of the program, continued exposure to part-time faculty could offer an alternative to full-time practice for residents who are considering other aspects of their careers such as research or administration.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25] Compared to our review of the 2013 literature relevant to general medicine educators, 26 we found more multi-institutional studies of high quality. Similar to last year, resident continuity clinic and handoffs were areas of focus.…”
Section: Discussionmentioning
confidence: 98%